Episodic Hypersomnolence Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
A 4 year old child who had complex partial seizures alternating with sleep that presented as episodic hypersomnolence is reported from the Mayo Clinic, Rochester, MN.